(untitled) (Journal of actual problems of jurisprudence, 2019)
This article discusses the hot issues of legal regulation of ethnic migration, the definitions of law sources were reviewed, the migration law soursec were analysed, problematic issues in legal regulations of public relations for the realization of social and economic rights of oralmans were formulated, recommendations on the improvement of the legislation and its implementation in the given sphere were given in this article. Keywords: compatriot, integration, legal regulation, repatriation, immigrant, foreign experience.